Poly(3,4-ethylenedioxythiophene)/poly(bis(4-phenoxysulfonic acid)phosphazene) conductive composites: an alternative interfacial layer to PEDOT : PSS - Celebi, Elif Busra; Cameron, Joseph; Skabara, Peter J.; Hacivelioglu, Ferda (Royal Soc Chemistry, 2024)
Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT : PSS) is a popular solution-processable hole transporting layer used in organic semiconductor devices such as organic light-emitting diodes or organic photovoltaics. It has benefits such as suitability for orthogonal processing, tunable conductivity and smooth film formation, yet the PSS polyelectrolyte is prone to degradation, impacting device performance or lifetime. In this work we present the use of PEDOT blends with a poly(bis(4-phenoxysulfonic acid)phosphazene) (PSAP) polyelectrolyte and study the effect of the PEDOT : PSAP ratio on the composite material properties. A comparable doping level can be achieved in PEDOT : PSAP films with respect to PEDOT : PSS and, as a result, an appropriate electrical conductivity for use as a hole transport layer can be achieved. Finally, when applied in organic light-emitting diodes, the use of PEDOT : PSAP hole transport layers can boost the external quantum efficiency, highlighting the promising performance of PSAP polyelectrolyte in conductive blends. An alternative solution processable hole transport layer based on PEDOT have been developed and compared with the poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT : PSS).